Hubungan Status Ekonomi, Pengetahuan, dan Perilaku Seksual Pra Nikah dengan Pernikahan Dini di Kecamatan Selo Boyolali - Wijayanti, Vivi, Yuli Kusumawati, SKM.,M.Kes (Epid) (2017)
Early marriage is a problem related to adolescent reproductive health that can be at risk of cervical cancer and potentially give birth to children in the state of under nutrition. District Selo has the highest percentage of early marriage in Boyolali, which is 46% in 2016.The purpose of this research is to analyze the correlations of economic status, knowledge, and sexual behavior before married with early marriage at District Selo Boyolali. This type of research is an observational study with case control design. The population in this research were women who married first before the age of 20 years at District Selo Boyolali in 2016 which amounted to 101 people. The selection of sample with ratio 1: 1, in case group counted 76 respondents and control 76 respondents using proportional random sampling.Techniques of statistical test using Chi Square test for economic status, knowledge, and sexual behavior before married variables. The results showed that there was a correlation of economic status with early marriage (p-value=0.003, OR=6,489; 95% CI=1,805-23,327), there was a correlation of knowledge with early marriage (p-value=0,001; OR=3,375; 95% CI=1,722-6,616), and there is no correlation of sexual behavior before married with early marriage (p-value=0,080) in District Selo Boyolali.